Discrimination of mantle sources of mafic dyke swarms in the southern São Francisco Craton by using Zr/Nb-Zr/Y binary diagram - Chaves, Alexandre de Oliveira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
Concentrations of incompatible elements are sensitive to the mantle partial melting processes and the ratios of these elements, with no intense crustal contamination, are particularly useful in distinguishing sources of basaltic rocks crystallized from such partial melting processes, as they minimize the effects of magma fractionation. By using additional immobile elements, ratios also minimize metamorphic processes eventually imposed on these rocks. When Zr/Nb and Zr/Y ratios are plotted in binary diagram, different mantle sources of mafic dyke swarms subjected to different degrees of partial melting appear as individual correlation lines that match a signature of each. Thus, the Zr/Nb versus Zr/Y diagram becomes an important tool for discrimination of mafic dyke swarms of a given continental region, as exemplified here for the southern portion of the São Francisco Craton.